Salinity-tolerant dwarf cashew rootstock has better ionic homeostasis and morphophysiological performance of seedlings - Valéria F. de O. Sousa; Gisele L. dos Santos; Josemir M. Maia; Sebastião de O. Maia Júnior; João P. de O. Santos; José E. Costa; Anselmo F. da Silva; Thiago J. Dias; Sérgio L. Ferreira-Silva; Carlos A. K. Taniguchi (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Considering the cashew tree’s relevance and the limitations imposed by salinity stress in semi-arid regions, the use of alternatives capable of mitigating the harmful effects due to salinity is of great importance to the production sector. The use of grafted plants, especially with rootstock made of tolerant materials, influences the accumulation of toxic ions in leaves of grafted seedlings. Thus, the objective of this work was to evaluate morphophysiological characteristics and leaf concentrations of Na+, K+ and Ca+2 of combinations of scion and rootstock of early dwarf cashew, contrasting in terms of salinity tolerance. The experiment was carried out in a completely randomized design with five replicates, in a 4 × 3 factorial arrangement, corresponding to four dwarf cashew scion/rootstock combinations (self-graft CCP 09, CCP 09/CCP 76, self-graft CCP 76, and CCP 76/CCP 09) and three NaCl concentrations (0, 50, and 100 mM L-1). Height, number of leaves, leaf area, dry matter, tolerance index and leaf concentrations of Na+, K+ and Ca+2 were evaluated after 30 days of application of NaCl concentrations. The scion/rootstock combination CCP 76/09 showed tolerance to 50 mM L-1, due to the increase of leaf area and number of leaves. The scion/rootstock combination CCP 76/09 was more suitable, as it kept the leaf K+ concentration and had the lowest Na+ concentration.